2006
DOI: 10.1590/s0074-02762006000100011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of St. Louis encephalitis virus isolated from human in São Paulo, Brazil

Abstract: (Calisher et al. 1989). The genome of flaviviruses contains a single-stranded positive sense RNA, about 10,800 nucleotides long that encodes 10 distinct proteins in a single reading frame (Chambers et al. 1990). SLEV is the etiologic agent of St. Louis encephalitis, a disease of epidemiological importance in North America. This virus was first isolated in the United States of America (US) in 1933, during an outbreak, which occurred in St. Louis and Kansas City, Mo. (Muckenfuss et al. 1934). In the US intermitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
11
0
6
Order By: Relevance
“…In Brazil, three strains of SLEV have been isolated from the blood of patients who did not display neurological symptoms. Two patients from Pará, in the North of the country, presented with fever and jaundice, and one from São Paulo had clinical symptoms consistent with dengue fever [27–29]. Non-human SLEV infections have also been found in southeastern Brazil, where the virus was isolated from wild birds, rodents and sentinel mice during a surveillance program of arbovirus activity carried out in the state of São Paulo from 1967 to 1969 [27–29].…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, three strains of SLEV have been isolated from the blood of patients who did not display neurological symptoms. Two patients from Pará, in the North of the country, presented with fever and jaundice, and one from São Paulo had clinical symptoms consistent with dengue fever [27–29]. Non-human SLEV infections have also been found in southeastern Brazil, where the virus was isolated from wild birds, rodents and sentinel mice during a surveillance program of arbovirus activity carried out in the state of São Paulo from 1967 to 1969 [27–29].…”
Section: Resultsmentioning
confidence: 99%
“…Published SLEV sequences since 2001 include 12 isolates from the Coachella Valley in California (Reisen et al , 2002), two 2005 isolates from Argentina (Diaz et al , 2006) and one 2004 human isolate from Brazil (Santos et al , 2006). During our study, we have determined the E gene sequence of 25 isolates from Texas, one from Jamaica and two from California.…”
Section: Resultsmentioning
confidence: 99%
“…These authors hypothesized that the strain of SLE virus at São Paulo State was not virulent for humans and circulated mainly in the forested areas. However, Rocco et al (2005) reported the first isolation of SLE virus from a febrile human case suspected to be dengue in São Pedro in 2004 andSantos et al (2006) indicated that this isolated SLE virus belongs to genotype III, being closely related to an Argentinean strain isolated in 1979 from Culex spp. mosquitoes (Kramer & Chandler 2001).…”
Section: Discussionmentioning
confidence: 99%